Method for preparing asphalt-based hard carbon material by triple oxidation method

By introducing metal oxides, epoxy resin and glucose into the asphalt precursor, and using a triple oxidation method to prepare hard carbon materials, the problems of low sodium storage capacity and insufficient electrochemical performance of asphalt-based hard carbon materials in the existing technology are solved, achieving Efficient sodium storage and low-cost production.

CN119330335AActive Publication Date: 2025-01-21INST OF CHEM CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411489083.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

In the prior art, when asphalt-based hard carbon materials are used in the negative electrode of sodium ion batteries, the sodium storage capacity is low, the first Coulomb efficiency is low, the platform capacity is low, and the direct air oxidation or hydrothermal oxidation technology fails to ensure the full oxidation of asphalt, which limits the Improved electrochemical performance.

Method used

The triple oxidation method is used to introduce metal oxide, epoxy resin and glucose into the asphalt precursor to perform pre-oxidation, pre-carbonization and high-temperature carbonization to form a hard carbon material with high oxygen content and porous structure.

Benefits of technology

The sodium storage capacity and first Coulomb efficiency of pitch-based hard carbon materials are significantly improved, their electrochemical properties are enhanced, and production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330335A_ABST
    Figure CN119330335A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing an asphalt-based hard carbon material by a triple oxidation method, which comprises the following steps of: (S1) uniformly mixing asphalt serving as a carbon precursor with a metal oxide, epoxy resin and glucose to obtain a mixture; (S2) pre-oxidizing the mixture in an oxygen-containing atmosphere to obtain a pre-oxidized precursor; (S3) grinding the pre-oxidized precursor, and carrying out heating heat treatment in an inert atmosphere for pre-carbonization; (S4) rinsing the pre-carbonized material by using an acid solution, filtering and drying; and (S5) carrying out high-temperature carbonization on the dried material in an inert atmosphere or a hydrocarbon gas atmosphere to obtain the hard carbon material. The asphalt which is high in cost benefit and mature in technology is used as a main raw material, and the metal oxide, the epoxy resin and the glucose are added in the pre-oxidation process of the asphalt precursor to serve as an oxygen supply agent and a supplementary carbon source, so that the oxidation degree of the asphalt precursor is effectively improved; therefore, the sodium storage capacity, the initial coulombic efficiency and the cycling stability of the hard carbon material are remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery negative electrode materials, and specifically relates to a method for preparing asphalt-based hard carbon materials by a triple oxidation method. Background Art

[0002] In recent years, various secondary battery technologies have developed rapidly. Lithium-ion batteries, as one of them, have been widely used in equipment such as portable electronic products and new energy vehicles. However, due to the limited reserves of lithium resources, it is not suitable for large-scale energy storage. In contrast, sodium resources are abundant on the earth, the processing technology is simple and low-cost, and it has similar chemical properties to lithium, which makes sodium-ion batteries show great potential in large-scale energy storage applications. However, sodium ions cannot be embedded in the graphite layer as stably as lithium ions, so the graphite anode is not suitable for the ester electrolyte of traditional sodium-ion batteries. Fortunately, hard carbon materials, with their large interlayer spacing (0.37-0.42nm) and rich closed-pore structure, provide a good choice for Na + The reversible storage of lithium ions provides a significant effect, and can even provide an initial specific capacity of up to about 300 mAh / g. However, the precursors of hard carbon are usually resins and fine biomass materials, which makes the cost of hard carbon materials high, and has long been higher than the price of graphite anodes that can be used for lithium storage, making it difficult to give full play to the cost advantage of sodium ion batteries (SIBs).

[0003] Asphalt is a mature chemical product, composed of aromatic hydrocarbons and alkanes. It has many advantages such as significant price, output and stability. It has been widely used in the production of artificial graphite anode materials and has achieved significant economic benefits. However, when asphalt is used as a precursor to prepare secondary battery negative electrodes, it tends to form soft carbon with high crystallinity, and the sodium storage capacity is usually less than 100 mAh / g, which limits its development and utilization in SIB hard carbon negative electrodes. The existing technology generally uses direct air oxidation or hydrothermal oxidation technology to improve the electrochemical properties of hard carbon negative electrode materials. However, these methods fail to ensure the comprehensive oxidation of asphalt, so that the prepared hard carbon materials have a high degree of graphitization and less closed-pore structure, which has limited effect on improving sodium storage performance, and this method is less efficient. To the surprise of the inventors, adding a specific proportion of metal oxides as catalysts during the calcination and carbonization process can significantly optimize the electrochemical properties of asphalt-based hard carbon negative electrode materials. Summary of the invention

[0004] In view of the problems of low sodium storage capacity, low ICE and low platform capacity faced by asphalt-based hard carbon materials in the existing prior art when used as negative electrodes of sodium ion batteries, the present invention provides a double oxidation strategy for the preparation method of modified asphalt-based hard carbon materials to improve the sodium storage performance of asphalt-based hard carbon materials. By introducing metal oxides, epoxy resins and glucose into the asphalt precursor for triple oxidation, not only the oxygen content of the precursor is increased, but also in the subsequent calcination process, this increased degree of oxidation helps to form more micropores and pore structures, thereby increasing the active sites of the hard carbon and significantly improving its sodium storage capacity and first coulombic efficiency. The present invention provides a triple oxidation method for modifying the sodium storage performance, ICE and platform area capacity of asphalt-based hard carbon materials.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a pitch-based hard carbon material by a triple oxidation method comprises the following steps:

[0007] (S1) asphalt as a carbon precursor is mixed evenly with metal oxide, epoxy resin and glucose to obtain a mixture;

[0008] (S2) pre-oxidizing the mixture in an oxygen-containing atmosphere to obtain a pre-oxidized precursor;

[0009] (S3) grinding the pre-oxidized precursor and subjecting it to pre-carbonization by heat treatment at elevated temperature under an inert atmosphere;

[0010] (S4) washing the pre-carbonized material with an acid solution, filtering it, and then drying it;

[0011] (S5) Carbonizing the dried material at high temperature in an inert atmosphere or a hydrocarbon gas atmosphere to obtain a hard carbon material.

[0012] The inventors found that asphalt as a carbon source, combined with metal oxides, epoxy resin and glucose as oxygen suppliers, and epoxy resin and glucose can also serve as auxiliary carbon sources, can not only increase the degree of oxidation of asphalt, but also greatly limit the softening and molecular rearrangement during the carbonization process, inhibit graphitization, and promote the formation of disordered microstructure and closed pores.

[0013] Furthermore, in step (S1), the metal oxide is selected from at least one of ferric oxide, magnesium oxide, copper oxide, zinc oxide, manganese oxide, and titanium dioxide, and the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol S epoxy resin, and bisphenol F epoxy resin, and the epoxy value is 0.3-0.5.

[0014] Furthermore, the metal oxide is preferably magnesium oxide. The inventors unexpectedly found that compared with other metal oxides, the addition of magnesium oxide can obtain a hard carbon negative electrode material with the best sodium storage performance. We speculate that the possible reason is that the addition of magnesium oxide not only provides a certain oxygen source for the oxidation of asphalt, but also promotes the propagation of heat in the mixture system, and ultimately promotes the thorough oxidation of asphalt from the inside out. In addition, magnesium oxide will also promote the reaction of asphalt with molecular oxygen (O2) to produce peroxyl radicals (ROO·), which propagate oxidation chain reactions and ultimately convert part of the hydrocarbons in the asphalt into ketones, aldehydes and carboxylic acids. Magnesium oxide stabilizes the related transition states and intermediates, thereby improving the overall reaction rate and efficiency. Other metal oxides can also improve the electrochemical performance of hard carbon to varying degrees, but none of them are as significant as magnesium oxide.

[0015] Furthermore, in step (S1), the mass ratio of asphalt, metal oxide, epoxy resin and glucose is 100:30-50:20-30:20-30. The combination of the metal oxide, epoxy resin and glucose as an oxygen source, after being mixed with asphalt in a specific proportion, can prepare a hard carbon material with greatly improved electrochemical properties. The inventor speculates that the possible reason is that under the action of high temperature and metal oxide, the oxygen in the resin / glucose is absorbed by the asphalt during the precipitation process, thereby promoting the oxidation of the asphalt. Moreover, the relatively high degree of graphitized carbon produced by the asphalt is conducive to the transmission of Na ions into the closed pores generated by the high oxygen characteristics, thereby promoting the increase of the sodium storage capacity.

[0016] Furthermore, in step (S1), the asphalt material is selected from coal-based asphalt, petroleum asphalt and biomass asphalt.

[0017] Furthermore, in step (S1), the method of sufficient mixing is not particularly limited, including but not limited to ball milling, grinding, sand milling, etc. Preferably, ball milling is used, with a ball-to-material ratio of 10-20:1, a rotation speed of 400-700 rpm, and a ball milling time of 3-10 hours.

[0018] Furthermore, in step (S2), the oxygen-containing atmosphere refers to an oxygen content greater than 20%, such as air, oxygen, and a mixture of air and oxygen; the pretreatment is carried out in an oxygen-containing atmosphere, heating the temperature to 250-350°C at a heating rate of 2-10°C / min, and keeping the temperature for 5-20h.

[0019] Furthermore, in step (S3), the pre-carbonization is carried out in an inert atmosphere, with the temperature being increased to 500-800°C at a heating rate of 5-30°C / min and kept at that temperature for 2-5h, and the inert atmosphere is at least one of argon, helium and nitrogen.

[0020] Furthermore, in step (S4), the acid solution is hydrochloric acid, sulfuric acid, nitric acid, oxalic acid, phosphoric acid, etc., and the amount used is 1 to 5 times the molar mass of the metal oxide in step (S1). The purpose of acid solution leaching is to remove the metal impurities originally contained in the asphalt and added.

[0021] Furthermore, in step (S5), the hydrocarbon gas is selected from at least one of methane, ethane, propane, butane, ethylene, acetylene and toluene; preferably, calcination is performed in a hydrocarbon gas atmosphere, which is beneficial to further improve the primary efficiency and capacity of the hard carbon material.

[0022] Furthermore, in step (S5), the high temperature carbonization is carried out by heating the temperature to 1300-1600°C at a heating rate of 5-10°C / min and calcining the temperature for 2-10 hours. The heating rate in step (S3) pre-carbonization is relatively fast, which is beneficial to avoid melting of the asphalt and rearrangement of the molecules into soft carbon with a high degree of crystallization, which is not conducive to the storage of sodium ions and is not conducive to improving the material capacity.

[0023] The present invention proposes a preparation technology and application of a sodium ion battery negative electrode material based on asphalt. The present invention uses asphalt, which is cost-effective and technologically mature, as the main raw material. By adding metal oxides, epoxy resins and glucose as supplements of oxygen supply agents and carbon sources during the pre-oxidation process of the asphalt precursor, the oxidation degree of the asphalt precursor is effectively improved, thereby significantly enhancing the sodium storage capacity and initial coulomb efficiency of the hard carbon material. In addition, under the action of high temperature and metal oxides, especially magnesium oxide, the oxygen in the resin / glucose is absorbed by the asphalt during the precipitation process, thereby promoting the oxidation of the asphalt. Moreover, the relatively high degree of graphitized carbon produced by the asphalt is conducive to the transmission of Na ions into the closed pores generated due to the high oxygen characteristics, thereby promoting the improvement of the sodium storage capacity. The preparation technology is not only low-cost and easy to operate, but also has a high carbon yield, and is very suitable for mass production of hard carbon materials, which are then used as negative electrode materials for sodium ion secondary batteries. Metal oxides can not only promote the uniform transfer of heat during the pre-oxidation process of asphalt, but also provide additional oxygen atoms for the asphalt from the inside, and finally promote the thorough oxidation of the asphalt from the inside out. A higher oxygen content can prevent the melting and molecular rearrangement of the asphalt precursor during the carbonization process, promoting the disorder of its microstructure; in addition, a higher oxygen content can be removed during the carbonization process and form a closed-pore structure for sodium storage, thereby providing more sodium storage sites and obtaining a higher sodium storage capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the SEM image of the hard carbon material obtained in Example 1.

[0025] Figure 2 This is the TEM image of the hard carbon material obtained in Example 1.

[0026] Figure 3 This is a constant current charge and discharge curve diagram of a sodium ion battery provided in Example 1.

[0027] Figure 4 This is a cycle curve diagram of a sodium ion battery provided in Example 1.

[0028] Figure 5 This is the SEM image of the hard carbon material obtained in Example 1.

[0029] Figure 6 This is the SEM image of the hard carbon material obtained in Example 2. DETAILED DESCRIPTION

[0030] To make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be described in detail below. The following examples are convenient for better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified.

[0031] Example 1

[0032] (S1) Coal-based asphalt with a softening point of 130° C. is mixed with MgO, epoxy resin E41, and glucose in a mass ratio of 100:50:20:30, placed in a ball mill, the ball-to-material ratio is controlled to be 20:1, the ball mill speed is set to 450 rpm, the forward and reverse modes are used, and the ball mill is milled for 4 hours to obtain a mixed precursor.

[0033] (S2) placing the mixed precursor obtained in step (S1) in a muffle furnace, heating it in air at a heating rate of 5°C / min, a heating temperature of 300°C, a holding time of 10 hours, and obtaining a pre-oxidized precursor after cooling.

[0034] (S3) Grinding the pre-oxidized precursor in step (S2) into powder, and then calcining it in a tubular furnace at a heating rate of 5°C / min, rising to 700°C and keeping the temperature for 3 hours in an Ar gas atmosphere to obtain a pre-carbonized precursor, which is then ground and refined.

[0035] (S4) taking concentrated hydrochloric acid diluted 5 times according to a molar ratio of MgO:HCl of 1:1, mixing it with the pre-carbonized precursor, stirring it continuously for 24 hours, and then filtering and drying it to remove metal oxide impurities in the pre-carbonized precursor.

[0036] (S5) placing the pre-carbonized body in a high-temperature tubular furnace, introducing argon gas, and calcining in an argon gas atmosphere at a heating rate of 5°C / min. After heating to 1300°C, keeping the temperature for 3 hours, and cooling to room temperature, a hard carbon negative electrode material is obtained.

[0037] Figure 1 is a SEM image of the hard carbon material obtained in Example 1; Figure 2 This is a TEM image of the hard carbon material obtained in Example 1. It can be seen that the surface of the hard carbon material particles obtained in Example 1 is dense, flat and smooth, and no pore structure appears; however, a closed-pore structure formed by the accumulation of complete graphite-like layers can be observed in the TEM image. Figure 2 It was shown that the addition of metal oxides significantly affected the material structure during the preparation of hard carbon materials, resulting in a graphite-like layered structure and the formation of interconnected closed pores. This is mainly because the high oxygen content prevents the fusion of aromatic rings and the rearrangement of molecules during the pre-carbonization stage; at the same time, during the carbonization process, oxygen atoms and their nearby carbon atoms are removed, triggering the formation of defects and closed pores. This closed-pore structure helps to form metallic sodium clusters inside the hard carbon, and the increase in interlayer spacing is conducive to the migration of sodium ions between layers. Figure 5 This is the SEM image of the hard carbon material obtained in Example 1. Figure 6 This is the SEM image of the hard carbon material obtained in Example 2. Figure 5 and Figure 6 , hard carbon materials without the addition of metal oxides or epoxy resins present a more regular layered structure, which cannot provide sufficient space to support effective sodium storage.

[0038] Example 2

[0039] Other conditions and operations are the same as those in Example 1, except that in step (S1), the mass ratio of coal-based asphalt to MgO, epoxy resin E41, and glucose is 100:30:30:30.

[0040] Example 3

[0041] Other conditions and operations are the same as those in Example 1, except that in step (S1), the metal oxide is Fe2O3.

[0042] Example 4

[0043] Other conditions and operations are the same as those in Example 1, except that in step (S1), the metal oxide is ZnO.

[0044] Example 5

[0045] Other conditions and operations are the same as those in Example 1, except that in step (S1), the metal oxide is MnO.

[0046] Example 6

[0047] Other conditions and operations are the same as those in Example 1, except that in step (S1), the metal oxide is TiO2.

[0048] Comparative Example 1

[0049] Other conditions and operations are the same as those in Example 1, except that magnesium oxide is not added in step (S1).

[0050] Comparative Example 2

[0051] Other conditions and operations were the same as those in Example 1, except that epoxy resin E41 was not added in step (S1).

[0052] Comparative Example 3

[0053] Other conditions and operations were the same as those in Example 1, except that glucose was not added in step (S1).

[0054] Application Examples

[0055] Preparation and testing methods of negative electrode materials: The hard carbon negative electrode materials, SuperP, and binder CMC / SBR obtained in the above embodiments and comparative examples are mixed in a mass ratio of 94:2:4, and an appropriate amount of water is added to make a slurry to obtain a uniformly mixed electrode slurry; the prepared electrode slurry is evenly coated on a copper foil, and after drying, it is vacuum dried at 60°C for 12 hours and sliced; a metal sodium sheet is used as a counter electrode, a glass fiber is used as a diaphragm, and 1mol / L NaPF6 (the solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1) is used as an electrolyte, and a button battery is assembled in an argon-protected glove box. A constant current charge and discharge test is performed, with a current density of 20mA / g and a charge and discharge voltage range of 0.001-2.0V. The test results are shown in Table 1.

[0056] Figure 3 This is a constant current charge and discharge curve diagram of a sodium ion battery provided in Example 1. Figure 4 This is a cycle curve diagram of a sodium ion battery provided in Example 1. About electrochemical performance data:

[0057] Table 1 Electrochemical performance test of asphalt-based hard carbon negative electrode materials

[0058]

[0059] From the half-cell test results of each embodiment in Table 1, it can be seen that the capacity, first coulomb efficiency and cycle stability of the obtained hard carbon sample are significantly improved by adding a compound oxygen supply agent, i.e., a compound of metal oxide, epoxy resin and glucose during the preparation process. Among the various metal oxides, magnesium oxide shows the most excellent electrochemical performance improvement.

Claims

1. A method for preparing a pitch-based hard carbon material by a triple oxidation process, characterized in that: The following steps are involved: (S1) asphalt as a carbon precursor is mixed evenly with metal oxide, epoxy resin and glucose to obtain a mixture; (S2) pre-oxidizing the mixture in an oxygen-containing atmosphere to obtain a pre-oxidized precursor; (S3) grinding the pre-oxidized precursor and subjecting it to a heat treatment at an elevated temperature in an inert atmosphere for pre-carbonization; (S4) washing the pre-carbonized material with an acid solution, filtering it, and then drying it; (S5) Carbonizing the dried material at high temperature in an inert atmosphere or a hydrocarbon gas atmosphere to obtain a hard carbon material.

2. The preparation method according to claim 1, characterized in that: In step (S1), the metal oxide is selected from at least one of ferric oxide, magnesium oxide, copper oxide, zinc oxide, manganese oxide, and titanium dioxide, and the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol S epoxy resin, and bisphenol F epoxy resin, and the epoxy value is 0.3-0.

5.

3. The preparation method according to claim 1, characterized in that: The metal oxide is magnesium oxide.

4. The preparation method according to claim 1, characterized in that: In step (S1), the mass ratio of asphalt, metal oxide, epoxy resin and glucose is 100:30-50:20-30:20-30.

5. The preparation method according to claim 1, characterized in that: In step (S1), the asphalt material is selected from coal-based asphalt, petroleum asphalt and biomass asphalt.

6. The preparation method according to claim 1, characterized in that: Furthermore, in step (S2), the oxygen-containing atmosphere refers to an oxygen content greater than 20%, such as air, oxygen, and a mixture of air and oxygen; the pretreatment is carried out in an oxygen-containing atmosphere, heating the temperature to 250-350°C at a heating rate of 2-10°C / min, and keeping the temperature for 5-20h.

7. The preparation method according to claim 1, characterized in that: In step (S3), the pre-carbonization is carried out in an inert atmosphere, with the temperature being increased to 500-800°C at a heating rate of 5-30°C / min and kept at that temperature for 2-5h, and the inert atmosphere is at least one of argon, helium and nitrogen.

8. The preparation method according to claim 1, characterized in that: In step (S4), the acid solution is hydrochloric acid, sulfuric acid, nitric acid, oxalic acid, phosphoric acid, etc., and the amount used is 1 to 5 times the molar mass of the metal oxide in step (S1).

9. The preparation method according to claim 1, characterized in that: In step (S5), the hydrocarbon gas is selected from at least one of methane, ethane, propane, butane, ethylene, acetylene and toluene.

10. The preparation method according to claim 1, characterized in that: In step (S5), the high temperature carbonization is carried out by heating the temperature to 1300-1600°C at a heating rate of 5-10°C / min and calcining at this temperature for 2-10 hours.

Citation Information

Patent Citations

  • Hard carbon-metal oxide-soft carbon composite material and preparation method and application thereof

    CN107240680A

  • Hard carbon material, preparation method thereof and application of hard carbon material in sodium-ion battery

    CN114524425A

  • Preparation method of composite carbon source sodium ion battery hard carbon negative electrode material

    CN118206105A